Sfide della Valutazione nell’Apprendimento a Distanza - Mahfoudh Hadane; Mimene Benghalem (Aleph, 2024)
In the light of the importance of the evaluation theme, this document aims to examine the evaluation practices adopted within the Italian Studies department in the post-pandemic period. The main objective is to understand the challenges encountered and, essentially, to determine whether the tests adopted for distance evaluation allow us to identify the true level of Italian language learners in a specific manner.